The expanding clinical spectrum of autoinflammatory diseases with NOD2 variants: a case series and literature review - Karamanakos, Anastasios; Vougiouka, Olga; Sapountzi, Evdoxia; Venetsanopoulou, Aliki I.; Tektonidou, Maria G.; Germenis, Anastasios E.; Sfikakis, Petros P.; Laskari, Katerina (Frontiers in Immunology, 2024)
Objective: To assess the impact conferred by NOD2 variants on the clinical spectrum of patients with systemic autoinflammatory diseases (SAIDs) in Greece. Methods: Consecutive patients (n=167) with confirmed SAIDs who underwent screening by next generation sequencing (NGS) targeting 26 SAID-associated genes, and carried at least one NOD2 gene variant, were retrospectively studied. The demographic, clinical and laboratory parameters were recorded. Results: In total, 24 rare NOD2 variants in 23/167 patients (14%) were detected. Notably, 18 patients had at least one co-existing variant in 13 genes other than NOD2. Nine patients had juvenile-and 14 adult-onset disease. All patients presented with symptoms potentially induced by the NOD2 variants. In particular, the candidate clinical diagnosis was Yao syndrome (YAOS) in 12 patients (7% of the whole SAID cohort). The clinical spectrum of patients with YAOS (mean episode duration 8 days) was fever (n=12/12), articular symptoms (n=8), gastrointestinal symptoms (n=7; abdominal pain/bloating in 7; diarrhea in 4; oral ulcers in 3), serositis (n=7), and rash (n=5), while the inflammatory markers were elevated in all but one patient. Most of these patients showed a poor response to nonsteroidal anti-inflammatory drugs (n=7/9), colchicine (n=6/8) and/or anti-TNF treatment (n=3/4), while a complete response was observed in 6/10 patients receiving steroids and 3/5 on anti-IL1 treatment. Another 8 patients were diagnosed with either FMF (n=6) or PFAPA syndrome (n=2) presenting with prominent diarrhea (n=7), oral ulcers (n=2), periorbital swelling and sicca-like symptoms (n=1), or maculopapular rash (n=1). One patient had a clinically undefined SAID, albeit characterized by oral ulcers and diarrhea. Finally, one patient presented with chronic relapsing urticaria with periorbital edema and inflammatory markers, and another one had a Crohn-like syndrome with good response to anti-IL-1 but refractory to anti-TNF treatment. Conclusion: NOD2 variants were detected in 1 out of 7 SAID patients and seem to have an impact on disease phenotype and treatment response. Further studies should validate combined molecular and clinical data to better understand these distinct nosological entities.